2018
DOI: 10.3892/ol.2018.8073
|View full text |Cite
|
Sign up to set email alerts
|

MAP30 promotes apoptosis of U251 and U87 cells by suppressing the LGR5 and Wnt/β-catenin signaling pathway, and enhancing Smac expression

Abstract: Abstract. Significant antitumor activity of Momordica anti-human immunodeficiency virus protein of 30 kDa (MAP30) purified from Momordica charantia has been the subject of previous research. However, the effective mechanism of MAP30 on malignant glioma cells has not yet been clarified. The aim of the present study was to investigate the effects and mechanism of MAP30 on U87 and U251 cell lines. A Cell Counting Kit-8 assay, wound healing assay and Transwell assay were used to detect the effects on U87 and U251 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Farago et al (36) demonstrated that following inhibition of Gsk-3β activity, the Wnt pathway is activated to promote breast cancer cell proliferation. Jiang et al (37) demonstrated that the expression levels of pGsk-3β Ser9 are increased in lung cancer tissues, and that the expression levels of pGsk-3β Ser9 are negatively correlated with lung cancer prognosis. Gsk-3β is a key kinase that determines the phosphorylation of β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Farago et al (36) demonstrated that following inhibition of Gsk-3β activity, the Wnt pathway is activated to promote breast cancer cell proliferation. Jiang et al (37) demonstrated that the expression levels of pGsk-3β Ser9 are increased in lung cancer tissues, and that the expression levels of pGsk-3β Ser9 are negatively correlated with lung cancer prognosis. Gsk-3β is a key kinase that determines the phosphorylation of β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…The extract inhibited proliferation and induced apoptosis in human and mouse adrenocortical cancer cells, whereas extract from blueberry, zucchini, and acorn squash did not show any cytotoxic effect [45]. MAP30 inhibited cell proliferation, migration and invasion and induced apoptosis in the glioma cell lines U87 and U251 in a time-and dose-dependent manner [23]. The methanol extract of fruit inhibited cell proliferation and increased cisplatin sensitivity in the ovarian cancer cell lines A2780cp, A2780s, C13* and OV2008 [54].…”
Section: Other Cancersmentioning
confidence: 91%
“…Similarly, methanol extract of fruit inhibited sphere formation and expression of CSC marker DCLK1 and Lgr5 in colon cancer cells [34]. MAP30 reduced expression of the self-renewal Wnt pathway effector molecule β-Catenin and its target genes c-Myc and cyclin D1 in glioma and prostate cancer cells [23,62]. Thus, bitter melon may have potential therapeutic implications against different cancers through its action on CSCs.…”
Section: Inhibition Of the Cancer Stem Cell Populationmentioning
confidence: 97%
“…Cell Culture. U87 and HS683 cells are the most representative glioma cell lines [25,26] and are very sensitive to chidamide; therefore, they have been chosen in the present work. U87 and HS683 glioma cell lines were purchased from Cell Bank (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%